Patient-tailored reproductive health care - Tesarik, Jan; Mendoza-Tesarik, Raquel (Frontiers in Reproductive Health, 2022)
Patient-tailored reproductive health care represents an important challenge for the current practice of infertility prevention, diagnosis and treatment. This approach is based on the concept of precision medicine, taking into account genetic, epigenetic, metabolic and lifestyle characteristics of each individual patient. Even though this goal is still far from being wholly achieved, some aspects can already be put into practice nowadays. Personalization can be based on a comprehensive analysis and synthesis of the patients' personal and familial history, taking into account outcomes of previous assisted reproduction technique (ART) attempts, if available, and confronting these data with the past and the latest clinical and laboratory examination outcomes. As to the male fertility status, there is an urgent need for the inclusion of an accurate diagnostic workup of infertile men leading to the choice of the most adequate follow-up for each particular pathological condition. The follow-up of women who have become pregnant as a result of the ART attempt has also to be personalized. This should be done taking into account both the basic data extracted from the patient's file and those derived from the experience gathered during the latest attempt. Last but not least, the individual condition of each couple has to be taken into account when counseling the patients as to the urgency of the actions to be taken to resolve their fertility problem.